Interviewing K-12 education experts and elites - Trinidad, Jose Eos (Frontiers in Education, 2024)
Understanding education experts and elites is crucial in the context of their larger influence on education and the public’s greater skepticism and criticism of their work. This paper distinguishes between traditional and expert/elite interviews (EEIs), and highlights strategies for conducting them. Experts and elites have relatively broader influence, more synthesized but less situated knowledge, more embedded professional networks, and less anonymity than the lay public—and interviews need to adjust to these differences. To do so, researchers should consider strategies for (1) access, (2) trust, (3) preparation for interviews, and (4) asking sensitive and awkward questions in contexts of significant power disparities. The article ends with caveats and novel possibilities with using EEIs with traditional interviews, quantitative methods, and network data.